Human monkeypox infection threat: A comprehensive overview - Yue Kang; Yue Yu; Silu Xu (Public Library of Science (PLoS), 2023)
Background In addition to the COVID-19 waves, the globe is recently facing global monkeypox (MPX) outbreak. As the daily confirmed cases of MPX infection across epidemic and nonepidemic countries are increasing, taking measures to control global pandemic remains crucial. Therefore, this review aimed to provide fundamental knowledge for the prevention and control of future outbreaks of this emerging epidemic. Methods The review was conducted using PubMed and Google Scholar databases; the search terms used were "monkeypox," "MPX tropism," "replication signaling of MPX," "biology and pathogenicity of MPX," "diagnosis of MPX," "treatment of MPX," "prevention of MPX," etc. The update epidemic data were collected from the websites of the World Health Organization (WHO), United States Centers for Disease Control and Prevention (CDC), and Africa Center for Disease Control and Prevention (ADCC). High-quality research results published in authoritative journals were summarized and preferred cited. Excluding all duplicates, non-English published references, and irrelevant literature, totally 1,436 articles were assessed for eligibility. Results It is still difficult to diagnose the patient as MPX simply based on clinical manifestations; therefore, under this situation, employing polymerase chain reaction (PCR) technology to provide confirmed evidence for the diagnosis of MPX seems to be the preferred and indispensable strategy. The treatment approach for MPX infection is mainly symptomatic and supportive; anti-smallpox virus drugs including tecovirimat, cidofovir, and brincidofovir can be employed in severe cases. Timely identification and isolation of confirmed cases, cutting off dissemination routes, and vaccination of close contacts are effective measures to control MPX. Also, smallpox vaccines (JYNNEOS, LC16m8, and ACAM2000) can be under consideration due to their immunological cross-protection among Orthopoxvirus. Nevertheless, given the low quality and scarcity of relevant evidence of current antiviral drugs and vaccines, deeply seeking for the MAPK/ERK, PAK-1, PI3K/Akt signaling, and other pathways involved in MPX invasion may provide potential targets for the treatment, prevention, and control of the epidemic. Conclusions In response to the current MPX epidemic, the development of vaccines and antiviral drugs against MPX, as well as the rapid and precise diagnostic methods are still urgently needed. Sound monitoring and detection systems should be established to limit the rapid spread of MPX worldwide. Author summary The daily increasing reported cases of MPX infection have set off the alarm for a global pandemic. In this review, we report the history of MPX infection and the biology and pathogenicity of MPX. The report chronicles the viral tropism and the role of signaling in MPX infection. We also summarize the current diagnosis approaches, and the therapeutic options available for the treatment and management, all of which will bridge the knowledge gap on MPX infection, provide a theoretical basis for combating the outbreak.